Propagation of Lime by Stem Cuttings (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted during three consecutive years(2002, 2003 and 2004) to study the effects of season of the year, girdlingand planting interval after girdling on rooting of stem cuttings of“Baladi” lime {Citrus aurantifolia (Christm.) Swing.}. Three types ofstem cutting were used; namely, non-girdled and girdled apical and basalcuttings. All cuttings were collected from a single lime tree during thesummer, autumn and winter seasons of each year from non-girdled andgirdled branches at intervals of 2, 4, 6, 8 and 10 weeks after girdling.Cuttings were planted in sand soil in plastic trays and were kept under aplastic tent in a lath house. Cuttings planted during autumn and wintergave significantly higher percentage of rooted cuttings than the summerplanted ones. Also, girdled apical cuttings gave significantly high rootingpercentage compared to the girdled basal cuttings. On the other hand, nosignificant differences were obtained between planting intervals of 2, 4, 6,and 8 weeks after girdling, while cuttings taken 10 weeks after girdlinggave significantly higher rooting percentage than the other intervals. Itseems that temperature, relative humidity and the accumulative increasein quantity and quality of carbohydrates, root promoters and inhibitorsplay an important role, among other factors, in the rooting of lime stemcuttings.
Keywords: Lime (Citrus aurantifolia); propagation; stem cuttings; own- rooted trees